Surface keratin 1, a tumor-selective peptide target in human triple-negative breast cancer - Shih-Jing Yao; Farideh Amirrad; Elmira Ziaei; Azam Saghaeidehkordi; Moom R. Roosan; Kiumars Shamloo; Ajay Sharma; Rachita K. Sumbria; Surya M. Nauli; Christopher G. Bunick; Kamaljit Kaur (Scientific Reports)
Abstract Targeting drugs to cancer cells via overexpressed cell-surface receptors has emerged as an effective therapeutic strategy for several cancers. However, identifying cell-surface receptors that allow selective uptake of targeting ligands by cancer cells—while sparing normal cells—remains a challenge, especially for triple-negative breast cancer (TNBC), which lacks a well-defined receptor for targeted delivery. In this study, immunohistochemical (IHC) analysis revealed that human TNBC patient tissues have significantly higher levels of keratin 1 (K1) compared to normal breast tissues. Among TNBC tissues, grade 3 tumors showed significantly higher (threefold) K1 expression compared to grade 2 tumors. We analyzed human TNBC and normal mammary epithelial cells to detect K1 from cell lysates using three methods: mass spectrometry, peptide mass fingerprinting, and Western blot. TNBC cell lysates confirmed the presence and high expression levels of 67 kDa K1. Importantly, intact cells showed that K1 is uniformly present on the surface of TNBC cells, while no or minimal cell-surface K1 was found in normal mammary epithelial cells using immunofluorescence confocal microscopy. Further, we show that cell-surface K1 was utilized by TNBC-selective peptide 18–4 for its uptake via cell-surface receptor (K1)-mediated endocytosis in TNBC cells, and the presence of peptide 18–4 did not affect the assembly of endogenous cytoplasmic K1. Taken together, our results demonstrate that K1 is overexpressed in human TNBC, and cell-surface K1 represents a promising new target for directed delivery in TNBC using targeting ligands such as peptide 18–4.